ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT MENGGUNAKAN BENEISH M-SCORE MODEL (Studi Empiris pada Perusahaan BUMN Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Hany Nur Azizsyah; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
This study aims to examine the influence of elements in the fraud diamond theory on fraudulent financial statements in companies listed on the Indonesia Stock Exchange (IDX).The independent variables used in this study include financial stability, external pressure, personal financial needs, financial targets, industry nature, ineffective supervision, rationalization and capability. While the dependent variable used is financial statement fraud. This study has a population consisting of all non-financial state-owned companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The sample used was selected based on the purposive sampling method. The total sample of this study amounted to 95 company financial reports. This study uses the logistic regression analysis method in hypothesis testing.The results of this study indicate that financial stability has a proven positive effect on financial statement fraud. While other variables, namely external pressure, personal financial needs, financial targets, industry nature, ineffective supervision, rationalization and capability, have no proven effect on financial statement fraud.